The Differences of Top-Down and Bottom-Up to Improve Students’ Motivation in Listening through Songs - Novianty, Melisa - (Enrich: Jurnal Pendidikan, Bahasa, Sastra dan Linguistik, 2023)
The purpose of this research is to know the students’ motivation through differentiate how to use Top-Down and how to use Bottom-Up in listening through songs. This research used a descriptive method. The total sample was 26 students in Senior High School Gajah Mada 3 Palembang in academic year 2022/2023, South Sumatera. The writer gave 10 questions of questionnaire to know about the results of their motivation in learning English, especially, in listening skill. The results showed that 3.8% always like English language, 15.38% usually like English language, 7.69% often like English language, 46.1% sometimes like English language, 26.9% seldom like English language. In this case, this top-down and bottom-up were very useful for them to imrove their motivation in learning listening skill through song. Besides, the students can use top-down and bottom-up not only for English lesson, but also for another skill of English language.